Chemosensory Anhedonia in Patients With Schizophrenia and Individuals With Schizotypy: A Questionnaire Study - Li, Zi-lin; Huang, Gao-jie; Li, Ze-tian; Li, Shu-bin; Wang, Yi-le; Zhao, Jiu-bo; Wen, Jin-feng; Hummel, Thomas; Zou, Lai-quan (Frontiers in Psychiatry, 2020)
Anhedonia, the loss or decline of the ability to enjoy pleasure, is an important clinical characteristic of schizophrenia. Schizotypal traits refer to the appearance of subclinical symptoms of schizophrenia across normal people. Still, few studies have investigated chemosensory anhedonia in schizophrenia patients and schizotypy individuals. Seventy-one schizophrenia patients (SCZ), 162 schizotypy individuals (SCT) as selected by the Schizotypal Personality Questionnaire (SPQ), and 182 healthy controls (HC) participated in our study. We used the Positive and Negative Syndrome Scale (PANSS) to measure the clinical symptoms of schizophrenia patients. All participants completed the Chemosensory Pleasure Scale (CPS), which was used to assess participants’ smell and taste hedonic capacities. We found that the three groups differed in chemosensory anhedonia. The SCZ group presented more severe chemosensory anhedonia than the SCT group, and the SCT group presented more severe chemosensory anhedonia than HC group. We also found that chemosensory hedonic capacity was negatively correlated with negative schizotypal traits in the SCT group and negative symptoms in the SCZ group. Our results suggested that chemosensory anhedonia is an important characteristic of schizophrenia spectrum disorders.